The Challenges of the Implementation of Waqf at Malaysian Public Universities: An Analysis According to the Legal Perspective: (Cabaran Pelaksanaan Wakaf Universiti Awam di Malaysia: Suatu Analisis Menurut Perundangan di Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2018)
In Malaysia, waqf (Islamic endowment) has been implemented to a significant degree in institutions of higher learning, especially in public universities (UA). Due to its importance as an alternative instrument in generating income for UA survival, it has become one of the main agendas of the Government of Malaysia under the Ministry of Higher Education. However, its implementation is faced with a number of legal issues that need to be addressed appropriately by the country's authorities. This involves especially the need for the approval of the State Islamic Religious Councils (SIRCs/MAIN) as the sole trustees of waqf property in Malaysia,including that of the Federal Territories, to implement waqf, as well as the absence of tax incentives and reliefs to the waqf donors and UA institutions under the Income Tax Act 1967 (Act 53)which has made it difficult for waqf implementation in all UAs. This article discusses the problems faced today based on research undertaken concerning waqf using the qualitative method on the legal aspects involving higher educational institutions and the authors' experiences in handling waqf issues in Malaysia. The main findings are that these issues could be solved through some syariah and legal authorities of the Federal Constitution,waqf statutes, the Administration of Islamic Law statutes, as well as amendments to tax statutes, and the Council of Rulers.Keywords: waqf, laws, State Islamic Religious Councils, higher educational institutions, public universities, Ministry of Higher Education